Changes in skin surface temperature during muscular endurance indicated strain - An explorative study - Fröhlich, M.; Ludwig, O.; Kraus, S.; Felder, H. (International Journal of Kinesiology & Sports Science, 2014)
Introduction: Non-contact thermography enables the diagnosis of the distribution of skin surface temperature during athletic movement. Resistance exercise results in stress of required musculature, which is supposed to be measurable thermographically in terms of skin surface temperature change. Objective: This study aims to evaluate the application of thermography to analyze changes in skin temperature, representing specific muscle groups, during and after resistance exercise. Method: Thirteen male participants (age: 27.1 ± 4.9 years, height: 181.5 ± 5.7 cm, mass: 74.8 ± 7.4 kg) completed the study. On 5 separate visits to the laboratory, participants performed one of 5 resistance exercise to target specific muscles (M. pectoralis major, M. rectus abdominis, M. trapezius, M. erector spinae, M. quadriceps femoris). The exercise protocol consisted of 3 sets of 20 repetitions, with 1 minute rest between exercise sets. The average skin surface temperature above the muscle groups used was thermographically determined using standard methods at 7 time points; pre-exercise, immediately following each exercise set, and post exercise (2, 3, and 6 minutes after the finale exercise set). The measurement areas were standardized using anatomic reference points. Results: From an inferential statistical point of view, no significant change in the average temperature caused by the applied resistance training was found for the individual muscle groups over time at the individual measurement times (all P>0.08). However, thermography showed a characteristic chronological temperature curve for the five body areas between measurement times, as well as a distinctive spatial temperature distribution over the measurement areas. Discussion: Based on the thermographic image data and the characteristic temperature curve, it is possible to identify the primarily used functional musculature after device-controlled resistance training. Therefore, thermography seems to be suited for visually imaging functional musculature.